The Labor Market Status of Foreign Born Vietnamese Americans - Linus Yamane (Claremont McKenna College, Department of Economics, 2001)
Vietnamese Americans experience significant wage discrimination and occupational discrimination. Vietnamese men and women earn less than comparable non-Hispanic white Americans. Vietnamese men face discrimination in wages on the order of 10%, and this does not seem to vary significantly by region of residence or level of education. Vietnamese women face varying amounts of discrimination depending on their region of residence and their level of education. Vietnamese men and women are less likely to be promoted to managerial and supervisory positions than comparable non-Hispanic white Americans.
Keywords: 330